Temporal Trend in Maternal Morbidity and Comorbidity - Diab, Yara H.; Huang, Jim; Nehme, Lea; Saade, George; Kawakita, Tetsuya (American Journal of Perinatology, 2024)
Objective This study aimed to examine the temporal trends of severe maternal morbidity (SMM) in the U.S. population in relation to trends in maternal comorbidity.Study Design We performed a repeated cross-sectional analysis of data from individuals at 20 weeks' gestation or greater using U.S. birth certificate data from 2011 to 2021. Our primary outcome was SMM defined as the occurrence of intensive care unit admission, eclampsia, hysterectomy, uterine rupture, and blood product transfusion. We also examined the proportions of maternal comorbidity. Outcomes of the adjusted incidence rate ratio (IRR) with 99% confidence intervals (99% CIs) for 2021 m12 compared with 2011 m1 were calculated using negative binomial regression, controlling for predefined confounders.Results There were 42,504,125 births included in the analysis. From 2011 m1 to 2021 m12, there was a significant increase in the prevalence of advanced maternal age (35–39 [45%], 40–44 [29%], and ≥45 [43%] years), morbid obesity (body mass index 40–49.9 [66%], 50–59.9 [91%], and 60–69.9 [98%]), previous cesarean delivery (14%), chronic hypertension (104%), pregestational diabetes (64%), pregnancy-associated hypertension (240%), gestational diabetes (74%), and preterm delivery at 34 to 36 weeks (12%). There was a significant decrease in the incidence of multiple gestation (9%), preterm delivery at 22 to 27 weeks (9%), and preterm delivery at 20 to 21 weeks (22%). From 2011 m1 to 2021 m12, the incidence of SMM increased from 0.7 to 1.0% (crude IRR 1.60 [99% CI 1.54–1.66]). However, the trend was no longer statistically significant after controlling for confounders (adjusted IRR 1.01 [95% CI 0.81–1.27]). The main comorbidity that was associated with the increase in SMM was pregnancy-associated hypertension.Conclusion The rise in the prevalence of comorbidity in pregnancy seems to fuel the rise in SMM. Interventions to prevent SMM should include the management and prevention of pregnancy-associated hypertension.Key Points
Keywords: maternal morbidity; pregnancy-associated hypertension; obesity